Low Frequency Noise of Tantalum Capacitors. (2002) - Sikula, J.; Hlavka, J.; Pavelka, J.; Sedlakova, V.; Grmela, L.; Tacano, M.; Hashiguchi, S.
Abstract : A low frequency noise and charge carriers transport mechanism analysis was performed on tantalum capacitors in order to characterise their quality and reliability. The model ofTa − Ta 2 O 5 − MnO 2 MIS structure was used to give physical interpretation of VA characteristic both in normal and reverse modes. The self-healing process based on the high temperatureMnO 2 − Mn 2 O 3 transformation was studied and its kinetic determined on the basis of noise spectral density changes. The correlation between leakage current and noise spectral density was evaluated and noise reliability indicator was suggested. In normal mode the noise spectral density at rated voltage increases with second power of current and it varies within two decades for given leakage current value. In reverse mode there is only weak correlation and for given applied voltage, the leakage current for all ensemble varies only by one order, whereas the noise spectral density of the same samples spread in five orders.